2018
DOI: 10.3389/fonc.2018.00442
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of Regulatory CD4 T Cells in Oral and Oropharyngeal Cancer: A Systematic Review

Abstract: Background: Recruiting regulatory CD4 T cells (Tregs) into the tumor microenvironment is an important tumor escape mechanism. Diminishing these suppressive cells is therefore one of the targets of cancer immunotherapy. Selective depletion of Tregs has proven successful in enhancing anti-tumor immunity and therapeutic efficacy in multiple tumor types. However, the role of Tregs in oral/oropharyngeal cancers is unclear with conflicting evidence regarding the effect of these suppressive cells on tumor prognosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 65 publications
(439 reference statements)
2
27
0
Order By: Relevance
“…This might come from the diversity of CD4 + lymphocyte subtypes and their opposing functions. A systematic review on OSCC and OPSCC reported that most studies investigate the subset of regulatory T cells (CD4 + Foxp3 + ) and despite narrowing the range of CD4 + cell types, the results are still contradictory, with a third of the studies associating an increased regulatory T cell infiltration with a poor prognosis, while the other two-thirds reporting improved outcomes in these patients [ 40 ]. In our study, we found a significantly higher infiltration with CD4 + cells at the front of invasion compared to the intratumor compartment.…”
Section: Discussionmentioning
confidence: 99%
“…This might come from the diversity of CD4 + lymphocyte subtypes and their opposing functions. A systematic review on OSCC and OPSCC reported that most studies investigate the subset of regulatory T cells (CD4 + Foxp3 + ) and despite narrowing the range of CD4 + cell types, the results are still contradictory, with a third of the studies associating an increased regulatory T cell infiltration with a poor prognosis, while the other two-thirds reporting improved outcomes in these patients [ 40 ]. In our study, we found a significantly higher infiltration with CD4 + cells at the front of invasion compared to the intratumor compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The current trial of OX40 agonist demonstrated an increase in TILs and improvement in the patients with an adequate safety profile [ 22 ]. However, the effect of immune checkpoint blockade therapy on OSCC is limited and the subtypes within the TILs and expression of immune cell subtypes should be also taken into account [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines induce apoptosis of tumor cells and/or activation of anticancer immune responses (16). CD4 + T helper cells also contribute to the cytotoxic anticancer immune response mediated by CTLs, by stimulating CTL priming through the release of cytokines, particularly IFN-γ (17).…”
Section: Anti-tumor Immune Responsementioning
confidence: 99%